1977
DOI: 10.1093/ajcn/30.12.2033
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and potassium intakes and excretions of normal men consuming sodium chloride or a 1:1 mixture of sodium and potassium chlorides

Abstract: Two groups of 10 healthy young men were matched on the basis of their free-choice consumptions of regular table salt. For 28 days they were then fed carefully controlled low-sodium foods. One group was permitted free-choice seasoning of these foods with regular table salt, the other with a 1:1 mixture of sodium and potassium chlorides. Intakes and urinary and fecal excretions of sodium and potassium were determined by analysis. The results were: 1) the subjects salted their food with essentially the same amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 7 publications
2
33
1
Order By: Relevance
“…41,42 Moreover, it is comparable to the increase in UCa seen in intervention studies in which individuals' dietary sodium intake is altered. 19,20,41 As UNa reflects sodium intake when subjects are in balance, 43 these intervention studies suggest that differences in sodium intake are the likely cause of the association between UNa and UCa.…”
Section: Discussionmentioning
confidence: 97%
“…41,42 Moreover, it is comparable to the increase in UCa seen in intervention studies in which individuals' dietary sodium intake is altered. 19,20,41 As UNa reflects sodium intake when subjects are in balance, 43 these intervention studies suggest that differences in sodium intake are the likely cause of the association between UNa and UCa.…”
Section: Discussionmentioning
confidence: 97%
“…3 It is likely, therefore, that for some number of days greater than 3 and less than 28, measurement of sodium intake from analysis of food portions would provide valid estimates of urinary excretion of sodium in individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, when intake and urinary excretion of sodium were averaged over a period of 28 days, they were almost identical in 10 young men with relatively low sodium intake, and were highly correlated in 10 young men with moderate sodium intake. 3 Other studies have reported wide fluctuations in 24-hour urinary sodium excretion in subjects on constant sodium intakes. 4 -5 Several factors have been identified that influence this variability: oscillation of balance for water and electrolytes, 8 level of sodium intake, 5 level of potassium intake, 1 degree of hydration, 7 and the delay in equilibration following a change in intake.…”
mentioning
confidence: 96%
“…KCl has physicochemical properties closely resembling NaCl, but some consumers might experience an unpleasant aftertaste. However, it was reported (Mickelsen et al, 1977) that a mixture containing equal amounts of NaCl and KCl tasted similar to that of pure NaCl.…”
Section: Introductionmentioning
confidence: 97%